Ser criança: um estudo etnográfico sobre as práticas infantis no Parque Santa Filomena, Jangurussu, Fortaleza – CE - Araújo, Francimara Carneiro (2015)
The aim of the present paper is to conduct etnography on what it is like to be a child in Parque Santa Filomena and how the childhood experience is conceived by two generational universes: the children’s a and adult’s one. In this regard, children were prioritized as interlocutors, questioning the adult-centric model, which even in the researches about children conceive them from an adults’ perspective. Parque Santa Filomena is a community within Jangurussu, Fortaleza-ce, stigmatized by the fact it was founded around a landfill and by being represented by the mainstream media as a territory with high violence rates. Such representation influences the way adults conceive childhood, who become mobilized by the fear of violence and, in conjunction with the institutions attended by children, adopt practices of great control and disciplining as a way to prevent from a violent become and to build and “ideal adult”. Nonetheless, children resist to the “adult world” and create their own strategies to do what they like the most: playing on the streets! The act of playing is signified as a demarcation of childhood in the community by children, who are no longer children when they lose interest in this activity. The encounter between children and violence was also analyzed, as well as how this phenomenon is conceptualized by children and how they experience it, either as agents, victims or even spectators. Lastly this investigation relied on the current discussion towards the Anthropology of Children and the Sociology of Childhood. Nevertheless, other actors and schools of thoughts were sometimes accessed upon the Beckernian approach in the use of theories such as “toolbox”. As a way to get close to the studied reality, ethnography with participative observation was chosen and other complementary techniques were applied in the research, such as focus group, draws, photography, video and interview.